Science-islam integration in islamic elementary school: a development of islam-based thematic teaching material - Dian Andesta Bujuri (Jurnal Ilmiah Pendidikan Dasar)
This research aims to produce Islamic-based teaching materials that are valid and practical. The method used in this research is Research and Development (RnD). The development model used is ADDIE (Analysis, Design, Development, Implementation and Evaluation). The data in this research was obtained through expert validation questionnaires (material experts, design experts, and language experts), student response questionnaires, and teacher response questionnaires to the Islamic-based thematic teaching materials that have been developed. Product trials of teaching materials that have been developed were carried out on grade 5 students at Alamul Yaqin Islamic Elementary School of Palembang. Data analysis techniques are carried out by referring to standard criteria for the validity and practicality of teaching materials. The results of the research show that first, the Islamic-based thematic teaching materials developed are categorized as very valid. This is proven by the score of material validation results reaching a percentage of 100%, design validation results reaching 96.84%, and language validation results reaching 100%. Second, the Islamic-based thematic teaching materials being developed are categorized as very practical. This is proven by the response score of students in the small group reaching 91%, while the response score of students in the large group reached 96%. The score from the teacher's assessment of the product reached 92%. This research proves that the Islamic-based teaching materials developed are very valid and very practical, so they are suitable for use in the learning process in grade 5 Islamic Elementary School.